COLISEPTICEMIA IN BROILER CHICKEN FARM IN BATUNGSEL VILLAGE, PUPUAN DISTRICT, TABANAN DISTRICT, BALI - Anak Agung Sagung Massita Jenika Putri; I Gusti Ketut Suarjana; Ida Bagus Made Oka; I Ketut Berata; Gusti Ayu Yuniati Kencana (Buletin Veteriner Udayana, 2025)
Escherichia coli is the most common bacterial infection found in broiler chicken farms. Escherichia coli infection in poultry is generally systemic and causes bacteremia, so it is called colispticemia. Case reports were conducted to diagnose animals with protocol number 116/N/25 based on anamnesis data, clinical signs, epidemiology, anatomical pathology changes, and histopathological changes and examination in the bacteriology laboratory. 30-day-old white broiler chickens were taken from a farm owned by Mr. Rudi located in Batungsel Village, Pupuan District, Tabanan Regency. The clinical signs observed were that the chickens showed abdominal distension, were weak and did not want to eat, had slow growth compared to other chickens, diarrhea, dirt around the cloaca, shortness of breath and weight loss. After the case chicken died, a necropsy was performed, then organ samples were taken and fixed with 10% Neutral Buffered Formalin (NBF). Pathological examination of the anatomy found a layer of fibrin in the heart, liver and lungs. Tissue samples taken were brain, trachea, lungs, liver, heart, spleen, kidneys and intestines, then histopathological preparations were made with hematoxylin-eosin staining. The results of histopathological examination found infiltration of heterophilic inflammatory cells in the lungs, liver, kidneys and intestines, indicating that the case animals were infected with bacteria. Examination of samples in the bacteriology and mycology laboratories obtained positive results for Escherichia coli bacteria in heart, lung, liver and intestine specimens. It can be concluded that the case chickens were infected by E. coli bacteria or were attacked by Colisepticemia. There needs to be increased sanitation and strict biosecurity in chicken farms